(untitled) (Research, Society and Development, 2020)
Ameloblastoma is a tumor of odontogenic origin that most frequently affects the posterior region of the mandible, clinically presents characteristics such as: slow growth, expansion of the cortical and absence of symptoms. The solid or musical variant is the most common, requiring in these cases more invasive surgical treatment, thus decreasing the recurrence rates. In this work, we report a case of ameloblastoma in the posterior region of the right mandible, in a female patient, with an evolution of 6 months, presenting clinically with swelling in the affected and asymptomatic area. After clinical and imaging assessment of the case, the patient was offered two surgical procedures, the first for resection of the lesion with an anterior safety margin, preservation of the ipsilateral mandibular condition and installation of a reconstruction plate to maintain the mandibular framework. In a second surgical procedure, the reconstruction plate was removed, disarticulation and installation of a mandibular prosthesis. The patient has 3 years of postoperative follow-up, with no signs of recurrence of the lesion and without functional or aesthetic changes from the mandibular prosthesis. We can conclude with this case that an early diagnosis and correct treatment plan is necessary for an adequate therapeutic approach in this type of injury and that the mandibular prosthesis proved to be a viable alternative in cases of major resections and disarticulation and adult patients, not presenting, in this case, postoperative complications.